Family Relationships Associated With Communication and Testing for Inherited Cardiac Conditions. (November 2019) - Shah, Lisa L.; Daack-Hirsch, Sandra; Ersig, Anne L.; Paik, Anthony; Ahmad, Ferhaan; Williams, Janet
The purpose of this study was to identify characteristics of family relationships associated with communication of genetic risk and testing behaviors among at-risk relatives in families with an inherited cardiac condition. Data were collected from 53 patients and parents of children with an inherited cardiac condition through interviews, pedigrees, and surveys. Associations were examined among family relationship characteristics and whether at-risk relatives were informed about their risk and tested for disease. Of 1, 178 at-risk relatives, 52.5% were informed about their risk and 52.1% of those informed were tested. Emotional closeness, relationship quality, and communication frequency had significant bivariate associations with genetic risk communication. Communication frequency was associated with genetic risk communication and testing in multivariate models. This study provides new insight into the extent of genetic risk communication and testing in families with inherited cardiac conditions. Family relationships, especially communication frequency, are critical factors in family communication of genetic risk.